فاعلیة شبكات التواصل الاجتماعي والبرید الالكتروني في نشر الثقافة الكشفیةلدى لعاملین بالنشاط الكشفي في جامعات العراق - نيبال كريم عبد الله (الرياضة المعاصرة)
Social networking and e-mail are the main means of communication between individuals and the most important means of exchanging experiences, disseminating culture, collecting knowledge and building bridges of communication. These means enable rapid communication of information, as well as a means for researchers to learn about new research, knowledge and culture. This the purpose whenthe founders wasfoundedthe network This prompted the researcher to conduct a study on the effectiveness of social networks and e-mail in the dissemination of Scout culture and the goal of the research to: 1. Preparation of the Scout Culture Dissemination Program 2. Identify the effectiveness of social networks and e-mail in spreading Scout culture. The hypothesis of the research is: There are no statistically significant differences in the effectiveness of social networks and e-mail in the dissemination of Scout culture to the experimental group of pre-test and post-test. The researcher used the experimental method because it is suit for the nature of the study. The research sample reached (30) individuals working in the scouting activity in the Iraqi universities .the a program was prepared to spread the Scout culture through the social networks and e-mail and continued for two months by two lectures each week. Social networks and communication programs (Viber, Watss up, Messenger, etc.) and the lecture is sent through, and conducted the researcher test tribal and past experimental group to reach the results of the search and used the statistical system (spss) The researcher concluded that there are statistically significant differences in favor of the post-test. Thus, the null hypothesis was rejected. This indicates that there is effectiveness of social networks and e-mail in disseminating the scouting culture. The researcher recommends conducting a study similar to the current study of other specialties.